Semoventes em trâmite entre formas - Daniel Anderson Vitor Saraiva (2006)
This dissertation is about the visual expressions of three people. We consider that what theyproduce is not recognised as works of art because it does not have a discursive form and is notimmediately engaged with the contemporary world of Beaux Arts. From this starting point weintend to locate elements that might be relevant, in some way, to contemporary artistic debate.This involves the possibility of extracting, from an image, a glimpse of meaning that, in thecircumstances of its initial creation, was not inherente to it. As a point of reference for theirvisual production we make use of their contextualised written or oral pronouncements. Acommon thread to this is echolalia, not in the sense of morbid repetition, but rather ofcontinuous subjectivisation. We make use of the term self-moving with respect to Capô, Zoecaand Wagner, who produced the imagens to which reference is made. We use self-moving, inthis work, in a particular sense that is differente from its original meaning.